A Family for Christmas - Finlay, Linda (London Penguin Books, 2015)
Eliza is just thirteen years old when she is forced out of her home one freezing winter's night. Lost and alone, she struggles across the snowy moors before collapsing on the doorstep of the reclusive Fay, who slowly nurses her back to health. Eliza soon falls in love with the wilderness of her surroundings, discovering an unexpected talent for making medicines and perfumes from the abundant local flowers. Yet more than anything she longs for a real home - so when Fay urges her to take an apprenticeship as a perfumer in a distant town, Eliza is devastated. Especially when the position brings misery and puts her life in danger. But when a handsome young man invites Eliza into his heart, and his home, it looks like there might be a chance for Eliza to finally find a happy ending - and a family for Christmas.
Keywords: Apprentices